Efecto de la implementación de las NIIF para pymes en la presentación de los estados financieros empresa Inversiones Jesahel S.A.C. – Trujillo 2018 - Castro Urbina, Aleyda Mhercy (2020)
This research work raises the IFRS for SMEs affect the presentation of the Financial Statements in the company INVERSIONES JESAHEL SAC 2018, and the objective of the research is to “Determine the effect of the implementation of the IFRS for SMEs in the presentation of the financial statements of the company INVERSIONES JESAHEL SAC of the city of Trujillo year 2018 ”, presenting the following specific objectives: Identify the difficulties of the implementation of the IFRS for SMEs in the presentation of financial statements, apply the IFRS for SMEs and determine their effect in the variation of the items of the financial statements and the last objective is to compare the reasonableness of the financial information before and after the application of IFRS.The methodology used is descriptive - comparative and the research design is a single box. The techniques used for data collection were interviews applied to the manager and the accountant, documentary and financial analysis of the information obtained and the tabulation of tables in quantities and percentages.Through this investigation it was concluded that the IFRS for SMEs significantly affect the presentation of the Financial Statements, since after their adoption variations were generated in the accounting items, obtaining accurate and truthful financial information.